Reconstruction of advanced periacetabular metastatic lesions with modified Harrington procedure - (:unkn) unknown (My University, 2016)
0

Objective: The purpose of this study was to assess the outcomes of patients who had been treated by a modified Harrington procedure for advanced periacetabular metastases.Methods: Between 2006 and 2013, 16 patients with a mean age of 57 years (range: 28-73 years) were treated using a modified Harrington technique. Extensive (class II/III) periacetabular defects were due to metastatic carcinoma or multiple myeloma. Surgical procedure included total hip replacement and acetabular reconstruction using threaded pins, cemented acetabular reinforcement ring, and/or polyethylene cup.Results: All patients improved in regard to pain and walking ability. Mean preoperative and postoperative Musculoskeletal Tumour Society (MSTS) functional scores were 52.8% (range: 33.3-73.3%) and 72% (range: 56.6-90%), respectively (p<0.05). There were 5 (31%) early or late complications requiring additional surgery. Implant survival was 75% and 37.5% at 12 and 18 months, respectively. Mean survival of the patients was 21 months (range: <1-6 years). Six remained alive, with a mean survival of 27 months (range: 18 months to 5 years).Conclusion: This modified Harrington procedure can be used for reconstruction of advanced periacetabular metastatic lesions
Keywords: Cerrahi